Analisis Prosedur Pelaksanaan Analisis Jabatan di Bagian Organisasi Sekretariat Daerah Kabupaten Tuban Pada Jabatan Pelaksana Berdasarkan Perbup Nomor 79 Tahun 2022 - Dian Santana; Gamaputra, Gading (Universitas Negeri Surabaya, 2023)
This final project research is research that describes the implementation of the preparation of Job Analysis based on Tuban Regent Regulation Number 79 of 2022 concerning Guidelines for Job Analysis and Workload Analysis in the Government of Tuban Regency. In this study, it discusses changes in regulations regarding nomenclature of executor positions so that problems are found, namely the difficulty in grouping the latest position names, namely based on position class, several job analysis documents that are not in accordance with applicable regulations. In this study, researchers used theory on regulations, namely Bureaucratic Reform, State Civil Apparatus, State Civil Apparatus Management and Position Analysis at Tuban Regency Regulation Number 79 of 2022. This research is a descriptive study using a qualitative method. The results of this final project research are that the preparation of job analysis is carried out in the preparatory stage by coordinating with resource persons and the team for preparing job analysis and socializing the preparation of job analysis in all OPDs. The collection of job data includes the implementation of a job analysis desk which is attended by all OPDs throughout Tuban Regency, but there are still many employees who do not understand how to fill out the document. Position data processing is carried out in a structured manner using guidelines and the preparation of job maps is carried out after implementing the job analysis desk, but the content of job information is still found to be inappropriate. Position verification is carried out by re-checking the E-Anjab Abk Simona Ministry of Home Affairs application, where it is known that there are still discrepancies in the contents of the position information and the determination of the results of the job analysis is carried out for the issuance of a decision letter. Keywords: Executive Position, Additional Employee Benefits, Job Analysis